(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the prevalence of colorectal diseases in individuals undergoing health check-ups at Can Tho University of Medicine and Pharmacy Hospital during 2023 to 2024, and to describe factors associated with colorectal polyps. Subject and method: A cross-sectional descriptive study was conducted on 174 asymptomatic individuals who underwent colonoscopy as part of their health examination at Can Tho University of Medicine and Pharmacy Hospital from May 2023 to May 2024. Results: A total of 174 participants were included, with a mean age of 50.9 ± 11.55 years and a male to female ratio of approximately one to one. More than half of the participants had colorectal abnormalities detected by colonoscopy, with polyps being the most common lesion (38.5 percent). Most polyps measured less than ten millimeters and multiple polyps were frequently observed. Males had a higher likelihood of having polyps than females (51.1 percent versus 25 percent, OR = 3.14, p < 0.001). Histopathological evaluation showed that more than one third of the polyps were neoplastic. Neoplastic polyps were significantly associated with a family history of colorectal cancer and with a polyp size of at least five millimeters, with p values below 0.05. Conclusion: The detection rate of colorectal diseases was relatively high among asymptomatic individuals. Colonoscopy plays an important role in early detection, especially in men, middle-aged individuals, and those with a family history of colorectal cancer. Colonoscopy should be considered for inclusion in routine health screening programs for high-risk groups.